Enhancing Antifungal Treatment of Candida albicans with Hypericin-Loaded Nanostructured Lipid Carriers in Hydrogels: Characterization, In Vitro, and In Vivo Photodynamic Evaluation - Sato, Mariana Rillo [UNESP]; Oshiro-Junior, João Augusto; Rodero, Camila Fernanda [UNESP]; Boni, Fernanda Isadora [UNESP]; Araújo, Victor Hugo Sousa [UNESP]; Bauab, Taís Maria [UNESP]; Nicholas, Dean; Callan, John Francis; Chorilli, Marlus [UNESP] (MDPI, 2023)
Background: Vulvovaginal candidiasis (VVC) is a worldwide public health problem caused predominantly by the opportunistic polymorphic fungus Candida albicans, whose pathogenicity is associated with its morphological adaptability. To potentiate the treatment of C. albicans-induced VVC by an alternative method as photodynamic therapy (PDT), hypericin (Hy), a potent photosensitizer compound was incorporated into a nanostructured lipid carrier (NLC) and dispersed in hydrogel (HG). Methods: After preparation of the sonication process, an NLC loaded with Hy was dispersed in HG based on Poloxamer 407 and chitosan obtaining Hy.NLC-HG. This hydrogel system was physically and chemically characterized and its in vitro and in vivo photodynamic and antifungal effects were evaluated. Results: Through scanning electron microscopy, it was possible to observe a hydrogel system with a porous polymeric matrix and irregular microcavities. The Hy.NLC-HG system showed mucoadhesive properties (0.45 ± 0.08 N) and a satisfactory injectability (15.74 ± 4.75 N.mm), which indicates that it can be easily applied in the vaginal canal, in addition to a controlled and sustained Hy release profile from the NLC-HG of 28.55 ± 0.15% after 720 min. The in vitro antibiofilm assay significantly reduced the viability of C. albicans (p < 0.001) by 1.2 log10 for Hy.NLC-HG/PDT and 1.9 log10 for PS/PDT, Hy.NLC/PDT, and free RB/PDT, compared to the PBS/PDT negative control. The in vivo antifungal evaluation showed that animals treated with the vaginal cream (non-PDT) and the PDT-mediated Hy.NLC-HG system showed a significant difference of p < 0.001 in the number of C. albicans colonies (log) in the vaginal canal, compared to the inoculation control group. Conclusions: Thus, we demonstrate the pharmaceutical, antifungal, and photodynamic potential of hydrogel systems for Hy vaginal administration.
Keywords: antifungal agent; mucoadhesiveness; nanostructured system; photosensitizer; yeast